Contribuição de árvores nativas para pastagens agroecológicas de famílias agricultoras - Freitas, Aroldo Felipe de (2017)
The present study had as objective 1) to identify the criteria used by agricultural families in the Zona da Mata mineira in state of Minas Gerais, Brazil, for the selection of native trees for a consortium with cattle pasture and the benefits that these trees provide to the pasture agroecosystem; 2) to analyze the effects of native tree species on the quality of fodder under their canopy; 3) to analyze the effect of native tree species on the quality and microbiology of pasture soil. The study was carried out in the municipalities of Araponga, Carrancas and Divino/MG. Qualitative research data were recorded through participant observation and semi-structured interviews with the families of Zona da Mata mineira. The quantitative research was carried out with forage and soil sampling at different distances under and outside the canopy projection of the native leguminous species Dalbergia nigra, Inga edulis, Machaerium nyctitans and Machaerium stipitatum. The quality of the forage in the different distances of the trees was measured by their quantity, moisture content and Nitrogen. Soil samples were evaluated by pH, organic matter content, macro and micronutrients, moisture and diversity and spore density of arbuscular fungi. It was also evaluated the presence of symbiotic bacteria of the genus Rizobium and the effect of these on Inga edulis seedlings in a greenhouse experiment. The averages of the quantitative data were compared statistically by the Scott-nott test. The producer families use as criterion of choice of trees for pasture consortium and the benefits that they generate for the property as a whole. These families consider that the consortium of trees with pasture can generate improvement to the beauty of rural property, environmental conservation, food availability, income generation and cultural aspects. No forage loss was verified by the consortium with the four tree species, D. nigra, I. edulis, M. nyctitans and M. stipitatum, and there was also improvement in the Nitrogen content of the forage under the canopy of M. nyctitans and in the humidity of the forage under the canopy of M. stipitatum. There was also no evidence of worsening of the parameters evaluated for quality and density and diversity of arbuscular mycorrhizae in the pasture soil by the consortium with the trees, but there was an increase in soil moisture closer to M. nyctitans and M. stipitatum and on the Mg and sum of soil bases under the canopy of M stipitatum. No changes were observed in nodulation and development of seedlings cultivated with soil of different distances of ingá. Thus, it is recommended the consortium of native trees with pasture for the benefits verified in the present study and the multiple uses of the species recorded in the bibliography.